The Influence of Augmented Reality-Based Play Activities on Children's Social and Emotional Skill Moderated by Parental Involvement - Kusmaladewi; Jamil (Jurnal Penelitian Pendidikan IPA, 2026)
The study aims to analyze the influence of augmented reality (AR)-based play activities on children's social and emotional skills moderated by their parents' involvement. We employed a quantitative approach with a quasi-experimental design involving 30 children in Group B of Angkasa 3 Mandai Kindergarten, Maros Regency, in the 2024–2025 academic year. Data were collected through structured observation and questionnaires, then analyzed using descriptive statistics and moderated regression. The results showed that AR-based play activities positively and significantly influenced children's social and emotional development (β = 0.612; p < 0.05), and parental involvement significantly strengthened this influence (β = 0.289; p = 0.012). These findings confirm that the impact of AR learning in early childhood education will be more effective if supported by active parental involvement through continuous collaboration with teachers.